SPECTROPHOTOMETRIC METHODS FOR THE QUANTITATIVE DETERMINATION OF MEMANTINE HYDROCHLORIDE IN PURE FORM AND PHARMACEUTICAL FORMULATIONS - AMIN, ALI H.; EL SHEIKH, RAGAA; ABDEL FATTAH, GHADA M.; ALI, MOHAMMED; ABDELNABY, BASMA M.; GOUDA, AYMAN A. (International Journal of Applied Pharmaceutics, 2022)
Objective: Three simple, sensitive, accurate, and precise spectrophotometric methods have been developed and validated for the determination of Alzheimer’s disease drug memantine HCl (MEM) in pure form and pharmaceutical formulations. Methods: The method was based on the formation of charge transfer complex between MEM as n-electron donor and various π-acceptors quinalizarin (Quinz) in methanol, p-chloranilic acid (p-CA) and 7,7,8,8-tetracyanoquinodimethane (TCNQ) in acetonitrile as chromogenic reagents which showed an absorption maximum at 558, 532 and 840 nm using Quinz, p-CA and TCNQ, respectively. The optimization of the reaction conditions such as the type of solvent, reagent concentration and reaction time were investigated. Results: Under the optimum conditions, beer’s law is obeyed in the concentration ranges 4.0–24, 10–160 and 5.0–50 μg/mlusing Quinz, p-CA and TCNQ, respectively with good correlation coefficient (r2 ≥ 0.9995) and with a relative standard deviation (RSD% ≤ 1.11). For more accurate analysis, Ringbom optimum concentration ranges were found to be between 8.0–20, 15–140 and 10–45 μg/ml using Quinz, p-CA and TCNQ, respectively. The limits of detection were found to be 1.2, 2.70 and 1.45 µg/ml and the limits of quantification were found to be 4.0, 9.0 and 4.83 µg/ml for Quinz, p-CA and TCNQ, respectively. A Job's plot of the absorbance versus the molar ratio of MEM to each of the acceptors under consideration indicated (1:1) ratio. Conclusion: The methods were successfully applied to the determination of MEM in its pharmaceutical formulations and the validity assessed by applying the standard addition technique. Results obtained by the proposed methods for the pure MEM and commercial tablets agreed well with those obtained by the reported method.